ANALISIS BIBLIOMETRIK PERKEMBANGAN PENELITIAN MIKROPLASTIK PADA BIVALVIA - Kumaji, Syam S.; Lihawa, Fitryane; Hasim; Baderan, Dewi Wahyuni K.; Mahmud, Marike; Yusuf, Daud (Universitas Cokroaminoto Palopo, 2024)
This study examines the development trend of microplastics research in 2019 - 2024. The study aims to find out: (1) the development of the number of international publications on microplastics in the Science Direct database from 2019 -22024; (2) the number of core journals in international publications on microplastics; (3) types of articles in international publications on microplastics; (4) the development of international publications of research in the field of microplastics by subject/field; (5) Map of the development of international publications of research in the field of microplastics based on keywords (co-word). Data collection by searching through science direct with microplastic keywords in the period 2019 to 2024 using article titles, abstracts, and keywords. Data analysis for the development trends of international publications in the field of microplastics was analyzed using VosViewer software. The results showed that the development of growth in the field of microplastics between 2019 and 2024 indexed in Science Direct reached the highest peak in 2023, with the number of publications reaching 240 publications (25.67%). The journal Science of The Total Environment is a journal that published 821 international publications on microplastics. Furthermore, based on co-word analysis, the development of the instrumentation field can be grouped into 7 main clusters.